Prevalence of Sensorineural Hearing Loss in Pediatric Patients with Sickle Cell Disease: A Meta‐analysis. (22nd October 2020) - Strum, David; Kapoor, Elina; Shim, Timothy; Kim, Sunny; Sabetrasekh, Parisa; Monfared, Ashkan
Abstract : Objectives: To determine the prevalence of Sensorineural Hearing Loss (SNHL) attributable to Sickle Cell Disease (SCD) in the global pediatric population and to identify factors contributing to its severity. Study Design: Meta‐analysis. Methods: We performed a comprehensive literature search for scientific articles in PubMed, Scopus, CINAHL, Web of Science, and the Cochrane Library that reported the incidence of hearing loss in populations under 18 years of age with excluding studies analyzing patients on iron chelation therapy, adults, or those without objective audiological analysis. Results: We identified 138 initial studies with 17 selected for analysis after applying the exclusion criteria. A total of 1, 282 SCD patients and 553 controls were included in the meta‐analysis. There was a statistically significant increase in the prevalence of SNHL in children with SCD compared to the general population with a cumulative risk ratio of 3.33. Conclusion: This is the first systematic investigation of the relationship between SCD and SNHL in pediatric patients across the globe. The increased prevalence of SNHL in the pediatric SCD population warrants future research into the predictors of SNHL severity and merits routine audiometric monitoring of SCD patients to reduce the social and developmental morbidity of hearing loss at a young age. PROSPERO Registration #: CRD42019132601. Laryngoscope, 131:1147–1156, 2021